ONE-POT SYNTHESIS OF 2,4,5-TRIARYLIMIDAZOLES FROM KETO-OXIMES: CHARACTERIZATION AND EVALUATION OF ANTIMICROBIAL ACTIVITY - KRANTHI KUMAR T,; SREENIVASULU R, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Background and Objective: Imidazole scaffold is pervasive in pharmaceuticals and it possesses diverse type of biological activities, especially triarylimidazole derivatives are biologically prominent molecules which inspired the current investigation. The objective of the work is to synthesize 15 novel 2,4,5-triarylimidazole derivatives and evaluate their antimicrobial and antimycobacterial activity against selected bacterial and fungal strains. Methods: The title compounds 2,4,5-triaryl-imidazole were synthesized from the corresponding aryl aldehydes and keto-oximes through the cyclization to N-hydroxyimidazoles and reduced thermally to the different imidazole derivatives. Agar disc diffusion method is employed for the antimicrobial and antimycobacterial studies. Results: Fifteen novel 2,4,5-triarylimidazoles were synthesized in adequate yields and characterization of the molecules was done by detailed spectral analysis using advanced analytical support. Results disclosed that all the synthesized compounds were exhibiting antimicrobial properties. Compounds 3h, 3g, 3b, and 3m were stated to possess potent antimicrobial properties in the given bacterial and fungal strains. Conclusion: The current investigation results support the antimicrobial and antimycobacterial activity of the synthesized 2,4,5-triarylimidazole derivatives. Further, research is necessary to explore the mechanism involved in the antimicrobial activity.